Women's invisible work in disaster contexts: Gender norms in speech on women's work after a forest fire in Sweden - Danielsson, Erna; Eriksson, Kerstin (Disasters, 2022)
The aim of this study is to investigate what women do in disaster situations and how both men and women perceive and discuss the work of women. These patterns were evidenced in the stories that were told following the largest forest fire in the modern history of Sweden in July 2014. The study is based on 31 retrospective interviews with volunteers involved in combating the forest fire and concentrates on stories about the supportive work of women during this disaster. The results indicate that women were praised when they followed traditional norms but were denigrated when they performed what were viewed as male-coded tasks. The stories reveal norms concerning what a woman is and is not by focusing on women's age and clothing and by directly and indirectly questioning their abilities and authority. The norms are also rendered visible by the positive attention that women receive while describing doing what is expected of them
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; catastrophe naturelle; division sexuelle du travail; environnement; europe; normes de genre; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; stéréotypes de genre; suède; thématiques; travail

Après la charge mentale, la charge écologique ? Au vert avec la dessinatrice Emma - Vert (2021)
Grâce à ses bédés pédagogiques et engagées, elle a popularisé le concept de "charge mentale" avant de s'attaquer à un tas d'autres sujets compliqués, dont le climat. Avec la dessinatrice féministe Emma, nous avons discuté d'écologie au sein du foyer, de l'égalité femmes-hommes à l'épreuve de l'"effondrisme" et des petits gestes contre la fin du monde.
Keywords: 2000 à aujourd'hui; 2020-2029; anticapitalisme; approches et analyses; charge environnementale; charge mentale; charge émotionnelle; environnement; europe; france; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; travail invisible; violences

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences

Travailler la terre et déconstruire l’hétérosexisme: expérimentations écoféministes - Rimlinger, Constance (Travail, genre et sociétés, 2019)
À partir de l’ethnographie de trois lieux ruraux (deux fermes et un gîte) tenus par des femmes lesbiennes et/ou queer qui s’inscrivent dans une critique écologiste et anticapitaliste de la société tout en questionnant les normes de genre et de sexualité, nous interrogerons la signification de ces choix de vie alternatifs au regard de l’identité des actrices et de la manière dont ils enrichissent la compréhension de la constellation des mouvements écoféministes. Nous observerons qu’avec le déplacement de la ville vers la campagne, et du monde salarié vers l’agriculture de subsistance, elles doivent mettre en place de nouvelles stratégies pour lutter contre l’isolement et s’intégrer localement. Simultanément, ce retour à la terre leur offre de nouvelles possibilités d’émancipation, d’engagement et de soutien aux femmes et aux minorités. Le travail agricole, l’engagement féministe et la politisation du quotidien constituent les différentes facettes d’un même projet : celui de chercher une voie plus juste et plus durable pour notre société.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; approches et analyses; care; com5170; cours; discipline; environnement; europe; france; hétérosexisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; séparatisme lesbien; thématiques; travail; vie rurale; écoféminisme; écologie queer

Combattre maintenant les inégalités sexuées, sociales et territoriales dans les quartiers politique de la ville et dans les territoires ruraux fragilisés - Haut Conseil à l'Égalité entre les femmes et les hommes (2014)
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discipline; environnement; europe; france; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques; travail; urbanisme

Les femmes dans les associations du secteur environnement - Flahault, Erika (Femmes et villes, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; environnement; europe; france; militance; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; thématiques; travail